2022
DOI: 10.1002/anie.202115205
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Multiphoton Absorption of Zinc‐AIEgen Metal–Organic Frameworks

Abstract: A series of luminescent frameworks was synthesized from the selective combination of aggregation induced emission (AIE)-linker tetra-(4-carboxylphenyl)ethylene (H 4 TCPE) and Zn 2 + . Complex 1 was formed by the close packing of Zn-TCPE hinge, and isostructural complexes 2-5 were constructed by the linkage of Zn-TCPE layer and pillar ligands. These complexes exhibit highly efficient multiphoton excited photoluminescence (MEPL) and concomitant thirdharmonic generation (THG). The multiphoton absorption (MPA) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…37 recently, Vittal and co-workers synthesized five MOF complexes utilizing H 4 tcpe. 38 Surprisingly, one of the obtained complexes showed extremely large ησ (2) values (≈1.2 × 10 6 to 7.4 × 10 7 GM), which are among the highest ησ (2) values reported for MOFs/CPs up to date (Table 1). As a perspective, we aim to further develop the MPA efficiency of these CP materials by combining the presented strong multiphoton absorbing chromophores (H 4 sbcd and H 4 fbcd) with the topological approach published by Vittal and co-workers, 38 which will potentially lead to modular tunable MPA materials significantly outcompeting the state of the art.…”
Section: ■ Conclusion and Outlookmentioning
confidence: 72%
See 2 more Smart Citations
“…37 recently, Vittal and co-workers synthesized five MOF complexes utilizing H 4 tcpe. 38 Surprisingly, one of the obtained complexes showed extremely large ησ (2) values (≈1.2 × 10 6 to 7.4 × 10 7 GM), which are among the highest ησ (2) values reported for MOFs/CPs up to date (Table 1). As a perspective, we aim to further develop the MPA efficiency of these CP materials by combining the presented strong multiphoton absorbing chromophores (H 4 sbcd and H 4 fbcd) with the topological approach published by Vittal and co-workers, 38 which will potentially lead to modular tunable MPA materials significantly outcompeting the state of the art.…”
Section: ■ Conclusion and Outlookmentioning
confidence: 72%
“…Investigation of the MPA properties using the Z-scan technique showed that the three CPs exhibit high two-photon absorption cross-sections σ (2) of 10,415–33,355 GM, which are among highest cross-sections reported for MPA-active CPs (Table ). Very recently, Vittal and co-workers synthesized five MOF complexes utilizing H 4 tcpe . Surprisingly, one of the obtained complexes showed extremely large ησ (2) values (≈1.2 × 10 6 to 7.4 × 10 7 GM), which are among the highest ησ (2) values reported for MOFs/CPs up to date (Table ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Apart from their well-known applications in storage, catalysis, optics, etc., MOFs have shown great potential to be developed as a model NLO system with an elaborate combination of building blocks possessing optical nonlinearities. , Although several metal–organic materials have been investigated for large NLO responses, they are limited to a suspension or powder form, which restricts their applications in miniaturized single crystalline devices. Also, studies on single crystals of NLO active MOFs built from photophysical chromophore are scarce. Several variables such as scattering, particle size, and morphology play a role in multiphoton absorption in powder samples, thereby affecting the calculation of the multiphoton effective cross section, which can be avoided in single crystals. Furthermore, structural correlation and modulation of NLO behavior have mostly been demonstrated in two MOF-based NLO models. The important roles of chromophore density, stronger excitonic interactions, interpenetration, hydrogen bonding, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there are two pathways to construct this kind of molecule: one strategy is to lock AIE chromophore units within cages or networks, resulting in emissive materials by reducing phenyl rotation, but such a kind of AIE molecule is limited. The other strategy is using ACQ molecules as building blocks by incorporating bulky substituents into their scaffolds to avoid strong π–π stacking or arranging the ACQ molecules with the help of templates, such as organic–inorganic hybrid materials, , dendritic polymers, micelles, organogels, and biomaterials, to avoid the self-quenching. However, it remains difficult to satisfy both the high local density and symmetrical distribution of chromophores with a high fluorescence quantum yield and high stability as well as good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%